ISPD produces CDP-ribitol used by FKTN and FKRP to transfer ribitol phosphate onto α-dystroglycan - Isabelle Gerin (Nature Portfolio, 2016)
Mutations in genes required for the glycosylation of α-dystroglycan lead to dystroglycanopathies. Here, the authors show that three of these enzymes (ISPD, FKTN and FKRP) work together to attach ribitol phosphate to α-dystroglycan.